Coping Mechanisms of Mathematics Students During the COVID-19 Pandemic - Soriano, Mark Anthony (International Journal of Arts, Sciences and Education, 2024)
This study aims to explore and understand the coping mechanisms of Mathematics students during the COVID-19 pandemic to craft interventions for adaptive instruction in mathematics. It specifically sought to identify the challenges students faced with Mathematics education during the pandemic, investigate how tertiary students coped with learning Mathematics during this period, and determine the necessary interventions to improve Mathematics education under these circumstances. This study employed a qualitative, phenomenological research design to explore the challenges and coping mechanisms of Mathematics students during the pandemic. In-depth face-to-face and phone interviews were conducted to uncover the underlying meanings and emotions associated with the participants’ coping strategies. The qualitative data collected from these interviews were analyzed using Braun and Clarke’s Thematic Analysis. The findings indicate that during the COVID-19 pandemic, students encountered significant challenges in online mathematics education due to technological issues, distractions, and difficulties with digital literacy, which they addressed through strategies like using mobile data, finding better signal areas, and creating quieter study spaces. Despite their efforts, many faced frustration and decreased motivation, exacerbated by barriers to communication and collaboration with peers and teachers, highlighting the importance of effective time management and support from their community. This research project holds significance as it offers crucial insights into the challenges faced by Mathematics students and their coping mechanisms amidst the COVID-19 pandemic. These insights are pivotal for developing effective intervention programs and support systems aimed at sustaining educational continuity and ensuring quality during future crises. Furthermore, the findings will inform the implementation of resilient and adaptable educational practices tailored to meet the diverse needs of students in times of uncertainty.